Use of serum albumin levels and salivary biomarkers in assessing periodontal disease: a community hospital perspective - Ping-Chen Chung; Ta-Chien Chan (BMC Oral Health)
Abstract Background Periodontal status can be reflected in serum and oral biomarkers. Salivary biomarkers are novel screening tools for individuals with dentophobia or disabilities. This study aimed to explore the differences in SiLL-Ha results and serum albumin levels between clinical attachment loss (CAL) ≥ 5 mm (Group A) and CAL < 5 mm (Group B) as well as the influence of sex on these differences. Methods This study recruited healthy adults aged 35–80 years from a community hospital. Participants completed a demographic questionnaire. We collected the participants' medical history, including hypertension, diabetes mellitus (DM) and hyperlipidemia, from electronically stored medical records. Additionally, they underwent a collaborated saliva test, an oral examination including records of clinical attachment levels, and a blood test to measure albumin levels sequentially. Participants were divided into Group A and Group B based on a CAL cut-off point of 5 mm. Multivariable logistic regression was used to analyze associations between the SiLL-Ha results, serum albumin levels, periodontitis, and sex stratification. Results The mean age of the 231 participants was 64.4 years, and 58.4% were women. Older age, low serum albumin levels, and high blood levels of SiLL-Ha were associated with periodontitis. Among the women, age and blood level of SiLL-Ha output were significantly associated with periodontitis. Among men, serum albumin level was significantly associated with periodontitis. Participants with DM were less likely to have periodontitis, particularly females. Conclusions The saliva test is a noninvasive tool applicable not only in dental clinics but also in community settings. It is beneficial for self-monitoring of oral health and promoting health awareness and behavior.